Architectural Consideration for Gamified Learning Systems: An Exploration of Offline-First Progressive Web Application - Ivan Dwi Fibrian; Teguh Priyo Utomo; Indra Lukmana; Zainal Muttaqin (Register: Jurnal Ilmiah Teknologi Sistem Informasi, 2025)
This paper presents a detailed exploration of the architectural development of an offline-first Progressive Web Application (PWA) prototype, specifically designed for gamified learning systems. The core research involves the technical examination of the PWA prototype, emphasizing its architectural design and crucial offline capabilities in the context of gamification elements. The study highlights the critical architectural components necessary for offline-first PWAs in educational settings, including the usage of PWA service workers and caching mechanisms. Key gamification features were identified and integrated, differentiating between those suitable for offline settings (like Points Systems, Badges/Achievements, Progress Tracking) and those requiring online connectivity (like Global Leaderboards and Social Interactions). The prototype, built using the React frontend framework and Supabase BAAS for the backend, demonstrates the potential of offline-first strategies in educational technology. It provides practical insights into the challenges and opportunities of maintaining engaging, uninterrupted learning experiences, particularly in low-connectivity environments. In conclusion, while offline-first PWAs effectively support learning activities with intermittent internet access, the research suggests that a careful balance must be managed between robust offline functionality and the richness of dynamic online interactivity to fully maximize the benefits of gamification.